NEUTRALIZACIONES DE LA PONZONA DE ALACRAN - ANGUIANO, LG (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1943)
Injns of hepatic extract during the first 10 days of pregnancy resulted in a slight increase in macrocytes and a marked increase in megalocytes in the newborn mouse Injns during the middle or end of pregnancy resulted in a slight decrease in megalocyte
BOL INST ESTUD MED BIOL
Keywords: NEUTRALIZACIONES, PONZON A, ALACRAN; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; PATOLOGIA ANMAL